Testing the psychometric properties of the Finnish version of the cross-cultural competence instrument of healthcare professionals (CCCHP) - Laura Hietapakka; Marko Elovainio; Karolina Wesolowska; Anna-Mari Aalto; Anu-Marja Kaihlanen; Timo Sinervo; Tarja Heponiemi (BMC, 2019)
Abstract Background To test the validity of the Finnish version of the Bernhard et al.'s Cross-Cultural Competence instrument of Healthcare Professionals (CCCHP). Methods The study sample comprised registered nurses (N = 810) from the Finnish "Competent workforce for the future" -project (COPE). Exploratory factor analyses and structural equation modelling were applied to test structural validity of the CCCHP. Internal consistency of the sub-scales was evaluated using the Cronbach's alphas. Criterion validity was explored in terms of received education for multicultural work, perceived difficulty of patients, and job satisfaction variables. Results The revised version of the instrument including four (motivation/curiosity, attitudes, skills and emotions/empathy) of the five original dimensions provided satisfactory psychometric properties (internal consistency, a good model fit of the data). Of the four remaining competence sub-scales, motivation/curiosity, attitudes and emotions/empathy were associated with the amount of received education for multicultural work, and all with perceived difficulty of patients, and all but attitudes with job satisfaction. Conclusion This revised Finnish version of the CCCHP provides a useful tool for studies focusing on the healthcare personnel's cross-cultural competence in delivering effective and culturally sensitive healthcare services for patients from different cultures.